Influence of Manganese on the Microstructure and Mechanical Properties of Oxide Dispersion Strengthened Steels - 앤드류; 김정한; Minyoung Na; Hye Jung Chang; 박태성; 김형찬; 노상훈 (대한금속재료학회, 2019)
The effect of Mn content on the microstructure and the mechanical properties of oxide dispersion strengthened (ODS) steel were examined. It was observed that the addition of 25 weight % Mn to ODS25 resulted in the transformation of a full ferrite phase to an austenite and an εhcp-martensite phases. ODS0 steel without Mn addition contained fine Y-Ti-O oxide particle with high number density. In contrast, ODS25 contained TiMn2O4 and relatively coarser Y2Ti2O7 oxide particles with lower number density. The TiMn2O4 oxide particle showed a crystallographic orientation relationship with the matrix phase. In addition, high density of deformation twins was observed in tensile deformed ODS25 but absent in tensile deformed ODS0. ODS25 exhibited higher room temperature tensile ductility and Charpy impact energy compared with ODS0 steels.